Implementation of pre‐emptive testing of a pharmacogenomic panel in clinical practice: Where do we stand? - Peruzzi, Elena; Roncato, Rossana; De Mattia, Elena; Bignucolo, Alessia; Swen, Jesse J.; Guchelaar, Henk‐Jan; Toffoli, Giuseppe; Cecchin, Erika (British journal of clinical pharmacology, 2025)
Adverse drug reactions (ADRs) account for a large proportion of hospitalizations among adults and are more common in multimorbid patients, worsening clinical outcomes and burdening healthcare resources. Over the past decade, pharmacogenomics has been developed as a practical tool for optimizing treatment outcomes by mitigating the risk of ADRs. Some single‐gene reactive tests are already used in clinical practice, including the DPYD test for fluoropyrimidines, which demonstrates how integrating pharmacogenomic data into routine care can improve patient safety in a cost‐effective manner. The evolution from reactive single‐gene testing to comprehensive pre‐emptive genotyping panels holds great potential for refining drug prescribing practices. Several implementation projects have been conducted to test the feasibility of applying different genetic panels in clinical practice. Recently, the results of a large prospective randomized trial in Europe (the PREPARE study by Ubiquitous Pharmacogenomics consortium) have provided the first evidence that prospective application of a pre‐emptive pharmacogenomic test panel in clinical practice, in seven European healthcare systems, is feasible and yielded a 30% reduction in the risk of developing clinically relevant toxicities. Nevertheless, some important questions remain unanswered and will hopefully be addressed by future dedicated studies. These issues include the cost‐effectiveness of applying a pre‐emptive genotyping panel, the role of multiple co‐medications, the transferability of currently tested pharmacogenetic guidelines among patients of non‐European origin and the impact of rare pharmacogenetic variants that are not detected by currently used genotyping approaches.